BALANCED AMINO ACID NUTRITION IN SEPSIS WITH ORGAN FAILURE - Muralimova R., Ibragimov N. (Central Asian Journal of Medicine, 2025)
Background: Sepsis complicated by multiple organ failure (MOF) remains a critical challenge in intensive care. Adequate nutritional support plays a key role in modulating the metabolic response and improving clinical outcomes.Objective: To evaluate the clinical efficacy of parenteral nutrition enriched with balanced amino acid solutions in patients with sepsis and MOF compared to standard formulations.Methods: A total of 80 postoperative patients with sepsis and MOF were enrolled. The intervention group (n=43) received parenteral nutrition with balanced amino acids (Gepa, Nefro), while the control group (n=37) received standard amino acid solutions. Biochemical, hemodynamic, and clinical parameters were assessed over 14 days.Results: Patients receiving balanced amino acids showed earlier reductions in catabolism, improved protein metabolism (albumin, transferrin levels), lower inflammatory markers (CRP, fibrinogen), and better SOFA/APACHE II scores by day 14. Duration of mechanical ventilation and time to gastrointestinal recovery were shorter.Conclusion: The inclusion of balanced amino acids in parenteral nutrition significantly improved clinical outcomes in septic patients with MOF, emphasizing the value of personalized metabolic support in critical care.